Pemberdayaan Perempuan oleh Kelompok Perempuan (Dasawisma Sekar Melati) Kecamatan Imogiri Kabupaten Bantul - Meita Rahmawati (Lifelong Education Journal, 2021)
Women are always considered helpless especially in the economic field. Women need to be empowered so that they can break the assumption of the community that women are always underdeveloped. This research was conducted to find out about empowerment activities carried out by the Dasawisma group "Sekar Melati" RT 09. The research method used was descriptive qualitative. Participants in this study included group managers and also one group member. Participant data retrieval techniques were carried out through in-depth interviews. The results showed that members felt the benefits of this empowerment, especially in the economic field. Activities carried out are not only savings and borrow activities but also social gathering. Activities are carried out every oncea month on weekends at each beginning of the month. Activities carried out at the house of group members in turn and all process activities and evaluations led by group leaders are then recorded and delivered by the Secretary. However, the empowerment that has been implemented in the process does not run as expected. Member participation in every activity of the members needs to be empowered again through other activities so that the Dasawisma group is increasingly productive and more beneficial to members.